Consequential life cycle assessment of demolition waste management in Germany - Dierks, Christian; Hagedorn, Tabea; Mack, Theresa; Zeller, Vanessa (Frontiers in Sustainability, 2024)
Context: Bulk mineral waste materials such as construction and demolition waste are Germany's largest waste stream. Despite the availability of high-quality recycling pathways such as road base layers, waste concrete is predominantly recycled into lower-quality recycling pathways like earthworks or unbound road construction. This is due to low demand for recycled aggregates in road base layers and frost protection layers, especially in public procurement. Purpose: This study assesses the environmental consequences of increasing high-quality recycling of waste concrete in the near future to provide decision support for public procurement in Germany. The focus lies on climate change due to its importance for decision makers. However, 17 other impact categories were assessed to avoid problem shifting. Methods: Life cycle assessment (LCA) is applied with background data from ecoinvent 3.9.1. Impact assessment was conducted at midpoint level using IPCC 2021 and ReCiPe Midpoint (H). Foreground data was taken from literature and expert interviews. In line with the goal of this LCA, a consequential modelling approach was followed to account for changes in the material flow system. Substitution creates a cascade effect previously omitted in consequential LCA studies, in which lower quality recycling materials replace higher quality recycling materials in their respective utilization pathways. Results and discussion: Increasing the high-quality recycling of waste concrete into road base layers causes a reduction in environmental impacts for all 18 impact categories, as it replaces natural aggregate and avoids backfilling of mixed mineral waste and excavated earth through substitution effects. Transport distances and ferrous metal recovery were identified as hot spots. Sensitivity analyses show that only transport is a significant issue. Conclusions: Increasing the highquality recycling of waste concrete in Germany is recommended in terms of environmental impacts. Lower-quality recycling is environmentally feasible only in cases where the avoided transport distances for natural aggregates and backfilling are significantly lower than the additional transport distances for high-quality recycling.